Sequence Analysis of the Genome of Piscine Orthoreovirus (PRV) Associated with Heart and Skeletal Muscle Inflammation (HSMI) in Atlantic Salmon (Salmo salar) - Markussen, Turhan; Dahle, Maria Krudtaa; Tengs, Torstein; Løvoll, Marie Therese; Finstad, Øystein Wessel; Wiik-Nielsen, Christer R.; Grove, Søren; Lauksund, Reidunn Silje; Robertsen, Børre; Rimstad, Espen (PLoS ONE, 2013)
Piscine orthoreovirus (PRV) is associated with heart- and skeletal muscle inflammation (HSMI) of farmed Atlantic salmon (Salmo salar). We have performed detailed sequence analysis of the PRV genome with focus on putative encoded proteins, compared with prototype strains from mammalian (MRV T3D)- and avian orthoreoviruses (ARV-138), and aquareovirus (GCRV-873). Amino acid identities were low for most gene segments but detailed sequence analysis showed that many protein motifs or key amino acid residues known to be central to protein function are conserved for most PRV proteins. For M-class proteins this included a proline residue in m2 which, for MRV, has been shown to play a key role in both the formation and structural organization of virus inclusion bodies, and affect interferon-b signaling and induction of myocarditis. Predicted structural similarities in the inner core-forming proteins l1 and s2 suggest a conserved core structure. In contrast, low amino acid identities in the predicted PRV surface proteins m1, s1 and s3 suggested differences regarding cellular interactions between the reovirus genera. However, for s1, amino acid residues central for MRV binding to sialic acids, and cleavage- and myristoylation sites in m1 required for endosomal membrane penetration during infection are partially or wholly conserved in the homologous PRV proteins. In PRV s3 the only conserved element found was a zinc finger motif. We provide evidence that the S1 segment encoding s3 also encodes a 124 aa (p13) protein, which appears to be localized to intracellular Golgi-like structures. The S2 and L2 gene segments are also potentially polycistronic, predicted to encode a 71 aa- (p8) and a 98 aa (p11) protein, respectively. It is concluded that PRV has more properties in common with orthoreoviruses than with aquareoviruses.